Pinocchio Walt Disney's classic little golden book library. - Walt Disney Productions (New York : Golden Books, 2004)
Presents Disney adaptations of six classic stories, including a selection of Mother Goose rhymes.
Walt Disney's Bambi -- Walt Disney's Dumbo -- Walt Disney's Mother Goose -- Walt Disney's Pinocchio -- Walt Disney's Scamp -- Walt Disney's Three little pigs.
Title from container.
3.5
K-3
Keywords: Disney characters -- Literary collections; Disney characters -- Literary collections